2016
DOI: 10.3402/gha.v9.30704
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome and factors affecting time to recovery in children with severe acute malnutrition treated at outpatient therapeutic care program

Abstract: BackgroundThe outpatient therapeutic care program (OTP) of children with severe acute malnutrition (SAM) has been decentralized to health post level in Ethiopia since 2008–2009. However, there is a lack of evidence regarding treatment outcomes and factors related to the duration of stay on treatment after its decentralization to health post level.ObjectiveThis study was aimed to assess treatment outcome and factors affecting time to recovery in children with SAM treated at OTP.DesignHealth facility–based retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
66
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 14 publications
12
66
4
Order By: Relevance
“…The present study was consistent with the study done in Debre Markos and Finote Selam hospitals, and Northern India (20,28). However, this study is contrary to studies done in Malawi, Wolisso St. Luke catholic hospital, Gamo-Gofa Zone and Shebedido woreda OTP center (30,(32)(33)(34). This difference may be due to differences in research design, and health care setting.…”
Section: Discussionsupporting
confidence: 89%
“…The present study was consistent with the study done in Debre Markos and Finote Selam hospitals, and Northern India (20,28). However, this study is contrary to studies done in Malawi, Wolisso St. Luke catholic hospital, Gamo-Gofa Zone and Shebedido woreda OTP center (30,(32)(33)(34). This difference may be due to differences in research design, and health care setting.…”
Section: Discussionsupporting
confidence: 89%
“…The study in Burkina Faso found an overall treatment duration of 52 days for children admitted with a MUAC <115 mm or WHZ <-3, which is higher than the 42 days registered by the HFs in this study. The same length of stay (42 days) has been reported in other studies in Ethiopia, but they were based on a discharge criterion of 15% weight gain [36,37]. One of them found that considering MUAC, a discharge criterion could mean increased length of stays, since they found that 20.6% of the children who showed a 15% weight gain would still be considered acutely malnourished if a MUAC <115 mm criterion was applied [37].…”
Section: Discussionmentioning
confidence: 78%
“…In the current review, eight studies (21,(24)(25)(26)(31)(32)(33)(34) revealed the independent predictors of recovery rate using hazard ratios. The predictors which were reported by the original studies were diarrhea (21,25,31,33), age>24 months (26,32,33) However, diarrhea, no edema and Amoxicillin were found to be independent predictors of recovery rate (Figure 8). The recovery rate of SAM children with diarrhea 16% less likely compared with those children with no diarrhea (HR=0.8, 95% CI: 0.75, 0.94).…”
Section: Predictors Of Recovery Rate Of Sam Children In Ethiopiamentioning
confidence: 99%
“…In-addition, the determinants of treatment outcomes, particularly the predictors of recovery rate is not addressed comprehensively. Few studies (21,(24)(25)(26)(31)(32)(33)(34)(35) revealed as edema, diarrhea, deworming, giving antibiotics, vitamin A supplementation, and distance from OTP centers and age as the predictors of recovery of under-five children with SAM in OTPs of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%